Verification of permeability for ionic liquid into biological specimens by using a mass spectrometer. (29th June 2022) - Yamashita, Taiji; Miyamoto, Kenji; Yonenobu, Hitoshi
Abstract: The pretreatment method with ionic liquids (ILs) is convenient for scanning electron microscope (SEM) observation of biological specimens. It needs neither fixation nor vacuum vapor deposition of metals to prevent fracture, deformation and charge-up. Although it was pointed out that the reason why the specimens are not fractured or deformed under the vacuum without fixation is the penetration of the ILs into cells and replacement with the intercellular water of the specimen, the experimental results were not yet self-consistent. In this study, in order to verify this hypothesis, we investigated whether the components of 1-ethyl-3-methylimidazolium methylphosphonate ([EMIM][MePO3 ]) are detectable by using a time-of-flight secondary ion mass spectrometer (TOF-SIMS) and liquid chromatography. It was found that the components of [EMIM][MePO3 ] could be detected from inside of the biological specimens. Moreover, it was verified that there is no fracture and deformation of the specimen, whose residual concentration of the IL on the surface would be less than the limit of detection by TOF-SIMS. Therefore, these experimental results explicitly show that penetration of [EMIM][MePO3 ] into the specimen and subsequent replacement with the intercellular water inside the body is the reason for preventing fracture and deformation of the specimen under the vacuum.